2021
DOI: 10.1186/s12888-021-03239-6
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of empowerment on the relationship between global function and personal recovery among community-dwelling patients with schizophrenia: a cross-sectional study

Abstract: Background Functional degradation among community-dwelling patients with schizophrenia can negatively influence their recovery. Given the importance of patient empowerment during recovery, this study examined the mediating effect of empowerment on the relationship between global function and personal recovery among community-dwelling patients with schizophrenia. Methods This cross-sectional study recruited community-dwelling patients with schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Social functioning can be directly related to several of the CHIME processes for personal recovery which places an emphasis on establishing and maintaining meaningful relationships (connectiveness) and the ability to act and carry out ones wishes (empowerment). Interventions that focus on social recovery have been associated with improved functioning (Fowler, D, Hodgekins, J, French, 2019) whilst a recent study by Lee and colleagues found that empowerment was a mediator between functioning and personal recovery (Lee, T. K., Lee, K., Lu, M., Hsieh, 2021).…”
Section: Predictors Of Personal and Clinical And Recoverymentioning
confidence: 99%
“…Social functioning can be directly related to several of the CHIME processes for personal recovery which places an emphasis on establishing and maintaining meaningful relationships (connectiveness) and the ability to act and carry out ones wishes (empowerment). Interventions that focus on social recovery have been associated with improved functioning (Fowler, D, Hodgekins, J, French, 2019) whilst a recent study by Lee and colleagues found that empowerment was a mediator between functioning and personal recovery (Lee, T. K., Lee, K., Lu, M., Hsieh, 2021).…”
Section: Predictors Of Personal and Clinical And Recoverymentioning
confidence: 99%
“…This study found that the personal recovery score of psychiatric nursing home residents was lower than those of individuals diagnosed with schizophrenia who were living in the community (Lee et al, 2021), indicating that residents of psychiatric nursing homes may have a greater need for personal recovery. This study also found that, out of personal factors, only religion had an association with personal recovery.…”
Section: Discussionmentioning
confidence: 84%
“…This study recommends prioritizing the improvement of residents' empowerment, which may more effectively promote the personal recovery of residents than improving global function. Nursing care could and should focus more on empowerment strategies to assist residents to perceive personal needs, abilities and life goals and enable person‐centred care (Hasan, & Musleh, 2017; Lee et al, 2021). Psychiatric and mental health nursing should strengthen the empowerment care to improve personal recovery by building up the capacity of the individuals to take control of their health and well‐being, focusing on individuals' strengths and abilities, supporting and encouraging individuals' involvement in decision‐making, and promoting individuals' motivation for achieving goals (Winsper et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The study results showed that empowerment‐based illness management can effectively improve medication adherence and recovery in persons with schizophrenia, with the overall effect being moderate. Although previous literature has supported empowerment as a crucial factor that can help reverse negative outcomes (Lee et al, 2021), few studies have verified empowerment‐based illness management, and there has been a lack of specific understanding of the intervention connotations of empowerment. The present study contributed by combining the results of the participants reported in each article, providing a large sample size ( n = 859–1473) for effectiveness verification and providing specific empowerment‐based illness management connotations, which are helpful for nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…Empowerment is a vital element of medication adherence (Náfrádi et al, 2017) and personal recovery (Lee et al, 2021) because the conceptual attributes of empowerment are participation in change, ability enhancement, and self‐determination, which are associated with positive behavioural changes (Castro et al, 2016). Motivation and alliances are referred to as essential prerequisites for empowerment to occur, and the results of empowerment are self‐integration, improved quality of life, hope, and a sense of worth (Weisbeck et al, 2019), which lead to personal recovery.…”
Section: Introductionmentioning
confidence: 99%